Bone density and miniscrew stability in orthodontic patients - Samrit Vilas; Kharbanda Om Prakash; Duggal Ritu; Seith Ashu; Malhotra Varun (Sciendo, 2012)
Objectives: The purpose of this study was to evaluate bone density in buccal inter-radicular bone between second premolars and first permanent molars and its association with the clinical stability of miniscrews used for en masse retraction of anterior teeth in extraction cases.